Um modelo baseado em habilidades para formação de profissionais de DevRel - ANA ELISA DA SILVA CUNHA (2023)
Developer Relations is an organizational area responsible for maintaining synergy between developer communities and organizations. This area can be seen in companies like Amazon, Apple, Google, and Microsoft, with a business model based on software ecosystems (SECO). The lack of clarity regarding the nature and set of skills required for a DevRel professional can impact the ability to perform activities related to the professional and, consequently, the health of the ECOS. Both industry and academia have brought definitions of DevRel. However, there are not enough studies to consolidate a training model for DevRel. In this sense, this master’s work proposes to establish a model involving a set of steps, dimensions, roles, and skills for the training of DevRel professionals that is understandable, comprehensible and adjustable so that any person or organization can develop the skills inherent in the profession.